2022
DOI: 10.1088/1674-1137/ac2a1f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment *

Abstract: The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 69 publications
(117 reference statements)
1
6
0
Order By: Relevance
“…An important study [17] was carried out to complement the isobar analysis, with the purpose of benchmarking the sensitivities of different observables using the analysis code from the isobar analysis to analyze simulated data. Of particular note, this study compared ∆γ to a measurement involving the width of the R correlator [18] and found these methods to have very similar sensitivities to a CME signal; this conclusion was bolstered by analytical work in [17] comparing these observables. I conclude that such additional observables are good tools to double-check the results from ∆γ, but we should not expect any qualitatively different conclusions or better sensitivity to come from them.…”
Section: Isobars: Blind Analysis and Subsequent Workmentioning
confidence: 99%
“…An important study [17] was carried out to complement the isobar analysis, with the purpose of benchmarking the sensitivities of different observables using the analysis code from the isobar analysis to analyze simulated data. Of particular note, this study compared ∆γ to a measurement involving the width of the R correlator [18] and found these methods to have very similar sensitivities to a CME signal; this conclusion was bolstered by analytical work in [17] comparing these observables. I conclude that such additional observables are good tools to double-check the results from ∆γ, but we should not expect any qualitatively different conclusions or better sensitivity to come from them.…”
Section: Isobars: Blind Analysis and Subsequent Workmentioning
confidence: 99%
“…In 2018, the flexibility of the Relativistic Heavy Ion Collider (RHIC) enabled the Solenoidal Tracker at RHIC (STAR) [1] to embark on an ambitious effort to explore new physics possibilities through minute signature variations between two slightly different experimental setups, using high energy collisions of the two isobar nuclear species 96 44 Ru+ 96 44 Ru and 96 40 Zr+ 96 40 Zr [2]. If the variations could be demonstrated at a sufficient level of confidence, they would indicate the presence of the so-called Chiral Magnetic Effect, a possible explanation for the imbalance between matter and anti-matter in the known universe (see citations in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…If the variations could be demonstrated at a sufficient level of confidence, they would indicate the presence of the so-called Chiral Magnetic Effect, a possible explanation for the imbalance between matter and anti-matter in the known universe (see citations in Ref. [2] for more details). Given the potential for bias toward making a landmark discovery with implications spanning multiple fields of research, the Physics Advisory Committee for RHIC issued a directive during preparations that, to bolster faith in the integrity of the research and confidence in the experimental findings, the program be conducted with analyses blind to the different species until the results were settled and ready for publication.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the effects of finite T and µ, the influence of a strong magnetic field B is an exciting topic relevant to phenomenology in relativistic heavy-ion collisions, where strong magnetic fields are generated in non-central collisions [12][13][14][15][16][17]. Many studies have been conducted on the effect of magnetic fields on the QCD vacuum [18][19][20][21][22][23][24], and it has been determined that magnetic fields B act as a catalyst of dynamical chiral symmetry breaking [25][26][27].…”
Section: Introductionmentioning
confidence: 99%